TASPO Plans Trip to Europe Next Year - Unknown (Evening News)
Members of Trinidad All Steel Percussion Orchestra (TASPO) returned home to arousing cheers from hundreds of well-wishers after a successful tour of England and France. TASPO stated that they will be returning to Europe after the Carnival season. They were offered several engagements to play in Belgium, Switzerland, Italy and the United States of America.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Entertainers -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Trinidad All Steel Percussion Orchestra -- History